2023
DOI: 10.1101/2023.02.02.526524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A synthetic signalling network imitating the action of immune cells in response to bacterial metabolism

Abstract: State-of-the-art bottom-up synthetic biology allows us to replicate many basic biological functions in artificial cell-like devices. To mimic more complex behaviours, however, artificial cells would need to perform many of these functions in a synergistic and coordinated fashion, which remains elusive. Here we considered a sophisticated biological response, namely the capture and deactivation of pathogens by neutrophil immune cells, through the process of netosis. We designed a consortium consisting of two syn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…In a related system, Walczak et al reported the adhesion of small C-star aggregates onto the surface of cell-size Giant Unilamellar Vesicles (GUVs), 48,53 observing that C-star particles are able to permeabilise liposomes and cause their rupture. To assess whether similar destabilisation occurs for SUVs depositing onto cell-size C-star condensates, we encapsulated calcein inside SUVs lacking phospholipid fluorescent labelling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related system, Walczak et al reported the adhesion of small C-star aggregates onto the surface of cell-size Giant Unilamellar Vesicles (GUVs), 48,53 observing that C-star particles are able to permeabilise liposomes and cause their rupture. To assess whether similar destabilisation occurs for SUVs depositing onto cell-size C-star condensates, we encapsulated calcein inside SUVs lacking phospholipid fluorescent labelling.…”
Section: Resultsmentioning
confidence: 99%
“…1820,43,44 Among condensate-forming DNA motifs, amphiphilic nanostructures, obtained by labelling DNA junctions with hydrophobic moieties, have shown significant potential owing to the stability of the self-assembled phases, their programmable nanostructure, and the possibility of engineering localised functionality and response to various environmental stimuli. 4553…”
Section: Introductionmentioning
confidence: 99%
“…Among the many design features that can be straightforwardly controlled are nanostar valency, flexibility and arm-length, all known to predictably influence self-assembly in analogous DNA systems [21,23,28,41,67]. Control over condensatesize could be achieved by co-transcribing monovalent, surface passivating RNA constructs [68,69]. Further RNA aptamers might be embedded to recruit molecular guests, including enzymes and metabolites, while ribozymes [70] could confer catalytic properties to the synthetic MLOs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found to physically interact with previously characterised including csrB/C, arrS and chiX, all of which have a role in cell survival in acidic conditions (Aiso et al, 2014;Babitzke & Romeo, 2007;Hayes et al, 2006). As the cells were cultured in M9LB which contains glucose, we expect fermentation and acidification of the media through-out batch culture (Walczak et al, 2023), suggesting a putative upregulation of these ncRNAs. Positionally enriched k-mer analysis (PEKA) (Kuret et al, 2022) revealed a preference for AU-rich k-mers seen in the cases of ncRNAs (Fig.…”
Section: Yfif As a Novel Rbp Fundamental For Bacterial Growthmentioning
confidence: 98%